Colonisation by Faecalibacterium prausnitzii and maintenance of clinical remission in patients with ulcerative colitis. Issue 2 (3rd June 2013) - Varela, E.; Manichanh, C.; Gallart, M.; Torrejón, A.; Borruel, N.; Casellas, F.; Guarner, F.; Antolin, M.
Summary Background Although incrimination of the intestinal microbiota in the pathogenesis of IBD is widely accepted, few data are available about the role of specific bacteria. Potentially, Faecalibacterium prausnitzii, bacteria with anti‐inflammatory properties, might be deficient in ulcerative colitis (UC). Aim To quantify F. prausnitzii in the faecal microbiota of UC patients in remission and determine its relationship with relapse. Methods A cross‐sectional study included 116 UC patients in remission, 29 first‐degree relatives and 31 healthy controls. A subset of eighteen patients, recruited during the first month of remission, underwent a 1‐year follow‐up. Total bacteria and F. prausnitzii were measured by quantitative Real Time PCR (qPCR, copies/g). Calprotectin was determined as inflammatory index (μg/g). Results We found that F. prausnitzii was reduced in patients (median, IQR: 1.4 × 108, 5.1 × 107–4.5 × 108) and relatives (1.7 × 108, 9.3 × 107–5.1 × 108) vs. controls (6.5 × 108, 3.7 × 108–1.6 × 109, P < 0.0001). Moreover, low counts of F. prausnitzii were associated with less than 12 months of remission (8.0 × 107, 2.0 × 107–3.5 × 108 vs. 2.1 × 108, 1.0 × 108–7.9 × 108, P < 0.001) and more than 1 relapse/year (8.0 × 107, 3.2 × 107–3.8 × 108 vs. 1.9 × 108, 6.8 × 107–6.0 × 108, P < 0.01). When patients were followed up, F. prausnitzii increased steadily until reaching similar levels to those of controls if remission persisted (2.9 × 108, 9.3 × 106–1.2 × 109; calprotectin: 76, 19–212), whereas it remained low if patients relapsed (2.2 × 108, 1.4 × 106–3.3 × 108; calprotectin: 1760, 844–3662 P < 0.05 vs. controls). Conclusions Defective gut colonisation by F. prausnitzii occurred in UC patients during remission and in their unaffected relatives. The recovery of the F. prausnitzii population after relapse is associated with maintenance of clinical remission.